Coronavirus disease 2019 attack rate in HIV-infected patients and in preexposure prophylaxis users. (1st October 2020) - Charre, Caroline; Icard, Vinca; Pradat, Pierre; Brochier, Corinne; Lina, Bruno; Chidiac, Christian; Cotte, Laurent
Abstract : Objective: A new coronavirus severe acute respiratory syndrome coronavirus 2 (SARS-Cov-2) emerged in China during late 2019 and resulted in the coronavirus disease 2019 (COVID-19) pandemic which peaked in France in March–April 2020. Immunodeficiency, precariousness and promiscuity could increase the risk of COVID-19 in HIV-infected patients and in preexposure prophylaxis (PrEP) users. No epidemiological data are available in these two populations. We report COVID-19 attack rate in HIV-infected patients and in PrEP users in the Rhône department, France, and compared it with the general population. Design: Retrospective analysis of a laboratory database. Methods: COVID-19 testing strategy in France was centered on symptomatic infections, hospitalized patients and symptomatic healthcare workers while most asymptomatic cases were not confirmed. SARS-CoV-2 positivity rate on PCR assays and COVID-19 attack rate were determined in HIV-infected patients and in PrEP users. COVID-19 attack rate in the general population was estimated from health authorities' database and demographic data. A corrected attack rate taking into account the laboratory representativeness was calculated. Results: From March to April 2020, 24 860 samples from 19 113 patients (HIV-infected 77, PrEP users 27, others 19 009) were assessed for SARS-CoV-2 PCR assay. The positivity rate appeared similar in HIV-infected patients (15.6%), in PrEP users (14.8%) and in other patients (19.1%). The crude/corrected COVID-19 attack rate appeared similar in HIV-infected patients (0.31/0.38%) and in PrEP users (0.38/0.42%), and of the same order as the estimated attack rate in the general population (0.24%). Conclusion: The risk of symptomatic COVID-19 in France appeared similar in HIV-infected patients and in PrEP users compared with the general population.